The Islands, Trinidad - (:unkn) unknown (My University, 2011)
The postcard shows a view of some of the small islands off the north western coast of Trinidad.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bodies of water--Trinidad and Tobago; Ocean--Trinidad and Tobago; Islands--Trinidad and Tobago